Accounting ratios and prediction of companies failure trading and service industry / Azlina Rahim, Anita Jamil and Zarinah Abdul Rasit - Rahim, Azlina; Jamil, Anita; Abdul Rasit, Zarinah (2004)
This study examines the use of accounting ratios as a prediction of company's failure in trading and services industry on the Main Board of Bursa Malaysia. The accounting ratios were calculated based on the information disclosed in the financial statements of the companies that were listed from 1991 to 2000. The study identifies the relationship between accounting ratios and companies failure. Four accounting ratios were selected and constructed. Each ratio represents the major categories namely liquidity, profitability, gearing and earning per share (EPS). The relevant data were obtained through analysis of annual reports In the Bursa Malaysia library. Further, the study attempts to find out which ratio was the best predictors to predict the company's failure and do the ratios provide information m decision-making process. The findings reveal that all the selected ratios were significant at P<0.01 and P<0.05 Thus, it can be concluded that all the four ratios that been selected were able to predict whether the company is success or failure. The results show that Liquidity ratio (Current ratio) and EPS tend to be the most powerful tool in measuring the performance of trading and service industry. In summary, this study concludes that all the four ratios in the study could be used as predictors for corporate solvency.